Patient Satisfaction of Surgical Treatment of Clitoral Phimosis and Labial Adhesions Caused by Lichen Sclerosus. Issue 4 (1st December 2015) - Flynn, Anne N.; King, Michelle; Rieff, Mollie; Krapf, Jill; Goldstein, Andrew T.
Abstract: Introduction: Lichen sclerosus (LS) is a chronic inflammatory dermatosis, usually affecting the anogenital skin in women. This chronic inflammation can cause scarring of genitalia including narrowing of the introitus and phimosis of the clitoris. These architectural changes can lead to recurrent tearing during intercourse (vulvar granuloma fissuratum) and decreased clitoral sensation. Surgical correction of vulvar granuloma fissuratum (VGF) and clitoral phimosis can be performed, but there is little data on the patient satisfaction and complications following these surgical procedures. Aim: To evaluate patient experience and outcomes in women undergoing surgical correction of scarring caused by anogenital LS. Methods: A retrospective chart review of patients at a vulvar disorders clinic was performed to identify women who had undergone surgical correction of clitoral phimosis or lysis of vulvar adhesions for VGF due to LS. Twenty‐eight women were contacted via telephone between 4 and 130 months postoperatively. An eight‐question survey was used to determine patient experience and outcomes. Main Outcome Measures: All participants completed an eight‐question survey to evaluate patient satisfaction with the surgery, effects on clitoral sensation, orgasm and pain with intercourse, postoperative symptoms or complications, and the presence of recurrent vulvar scarring. Results: Participants reported that they were either very satisfied (44%) or satisfied (40%) with the procedure. Of the women who experienced decreased clitoral sensation prior to surgery, 75% endorsed increased clitoral sensitivity postoperatively. Of the women who had dyspareunia prior to surgery, the majority of women reported having pain‐free sex (33%) or improved but not completely pain‐free sex (58%) after surgery. There were no complications or symptoms made worse by the surgical procedures. Conclusions: This study shows high patient satisfaction and low complication risk associated with surgical correction of clitoral phimosis and lysis of vulvar adhesions for VGF caused by LS. Patients reported improvement in clitoral sensation and ability to achieve orgasm, as well as decreased dyspareunia. Surgical correction of vulvar scarring is a viable option to restore vulvar anatomy and sexual function in appropriate candidates with anogenital LS.